In Search of Balance: Text, Data Mining and Copyright in the Digital Single Market Directive from a Fundamental Rights Perspective - Manteghi Maryna (Sweet and Maxwell, 2025)
Text and data mining (TDM) is integral to data-driven innovation. This advanced analytical technique allows users to generate new knowledge from the plethora of digital data. The EU regulation of TDM is based on mandatory exceptions provided under arts 3 and 4 of the Directive on Copyright in the Digital Single Market (DSM Directive). Even though these provisions have improved the regulation of TDM compared to the legal uncertainty that existed before the adoption of the DSM Directive, their effectiveness could be challenged in terms of fundamental rights. This article argues that the exceptions fail to take into account the freedom of information and the freedom of research in a balanced way. These fundamental freedoms have been only addressed superficially. The study raises constitutional concerns regarding the purpose limitation of art.3 and its narrow scope of beneficiaries, the “lawful access” requirement, the storage conditions, the “opt-out” mechanism of art.4, and the application of technological protection measures. In this regard, the article proposes amendments to the regulation of TDM so that the balance between the fundamental rights to information and research and the fundamental right to intellectual property would be realised better than in the current law. The findings of this article are crucial for developing efficient and consistent legal grounds for carrying out TDM at EU-wide level, which would enhance research and innovation across the EU Member States.